2018
DOI: 10.3390/s18113694
|View full text |Cite
|
Sign up to set email alerts
|

Sloshing Measurements inside a Liquid Hydrogen Tank with External-Heating-Type MgB2 Level Sensors during Marine Transportation by the Training Ship Fukae-Maru

Abstract: Recently, a project was initiated in Japan to transport a large amount of liquid hydrogen (LH2) from Australia to Japan by sea. It is important to understand the sloshing and boil-off that are likely to occur inside an LH2 tank during marine transportation by ship, but such characteristics are yet to be experimentally clarified. To do so, we combined the liquid level detected by five 500 mm long external-heating-type magnesium diboride (MgB2) level sensors with synchronous measurements of temperature, pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…In addition to selecting suitable materials for tank design, and minimising boil-off gas during transportation, 92,304 another key consideration in liquid hydrogen transport is sloshing. 304 This phenomenon is the movement of the liquid in the vessel due to the motion of the carrier, and it can lead to significant boil-off. Baffles may be installed in the tank to mitigate the effect.…”
Section: Liquid Hydrogen Transportmentioning
confidence: 99%
“…In addition to selecting suitable materials for tank design, and minimising boil-off gas during transportation, 92,304 another key consideration in liquid hydrogen transport is sloshing. 304 This phenomenon is the movement of the liquid in the vessel due to the motion of the carrier, and it can lead to significant boil-off. Baffles may be installed in the tank to mitigate the effect.…”
Section: Liquid Hydrogen Transportmentioning
confidence: 99%
“…The authors concluded that the increase rate of LH 2 temperature and tank pressure was large if the ship rolling angle was six degrees [125]. In 2018, Maekawa et al [146] used a similar setup always installed on the Fukae-Maru vessel to investigate the LH 2 temperature and pressure increase rates as well as the LH 2 sloshing within the tank during a zigzag maneuver. Measurements inside the LH 2 tank are very challenging due to the ultra-low temperature effect.…”
Section: Other Studies Related To Liquid Hydrogen For Maritime Applic...mentioning
confidence: 99%
“…The thermodynamic effects of sloshing in LH2 ships are also not widely investigated. Maekawa et al (2017) [30] and Maekawa et al (2018) [31] observed liquid level and temperature measurements for 0.02 m 3 of LH2 in a test ship subjected to manoeuvreinduced sloshing in several planes of motion. Wei et al [32] further investigated sloshinginduced pressure changes in the specific case of a tank filled with LH2.…”
Section: Introductionmentioning
confidence: 98%